The Effect of Forgiveness Therapy With Dhikr to Increase Self-Acceptance in People With Hiv/Aids at Surakarta - Reza Mina Pahlewi (Syntax Corporation, 2022)
This study aims to determine the effectiveness of forgiveness therapy (forgiveness therapy) with dhikr to increase self-acceptance in people with HIV/AIDS (PLWHA). The design of this study was a pre-experiment with a one-group pretest-posttest design model. The participants of this study were six PLWHA who had the characteristics of having been diagnosed with HIV/AIDS positively, had a low or moderate self-acceptance score, and were Muslim. Self-acceptance was measured using a self-acceptance scale of 28 items. The quantitative analysis test was carried out using the SPSS for Windows 16.0 computer program, while observation and interview techniques were used to obtain additional qualitative data. Quantitative data were analyzed using paired sample t-test. The results showed that there was a very significant difference in the level of self-acceptance before and after being given forgiveness therapy with dhikr with a value of t = -5.017 (p = 0.004; p < 0.01). The results of quantitative data analysis show that the level of self-acceptance of people with HIV/AIDS has increased after being given forgiveness therapy with dhikr so it can be concluded that forgiveness therapy with dhikr can increase self-acceptance in people with HIV/AIDS.